Mag-aabroad ka ba? application at employment manual ng overseas workers - Bermillo, Edmundo Dacara (Verbena Pub., 1990)
This book contains both illustrated and written information for workers who are desiring to be employed abroad which provides them an insight into the recruitment, hiring and deployment processes starting from their application for employment to the post-employment stage and finally when they return home for good or for renewal of their contract.